Правова структура та принципи побудови системи національної безпеки в Україні - Беззубов, Д.О. (Держава і право, 2011)
Пропонується
визначення
категорії
«система
національної
безпеки» та поділ
небезпек
за рівнем впливу
на суспільні процеси.
Розглядаються
загальні
та спеціальні
принципи
функціонування
системи
національної
безпеки,
розкривається
їх сутність та
зміст. Предлагаются
определения
категории
«система
национальной
безопасности» и
разделение
безопасности
по уровню
влияния
на общественные
процессы.
Рассматриваются
общие
и специальные
принципы
функционирования
системы
национальной
безопасности,
раскрывается
их сущность
и содержание. The Abstract: in article are considered problems of the legal building of the system to
national safety. They are offered determinations to categories system to national safety and
division on level of the influence upon public processes on active and passive types. They Are
Considered general and special principles of the operating the system to national safety,
opens their essence and contents. They Are Defined facility of the operating the system to
national safety of the Ukraine.